Implications of differing attitudes and experiences between providers and persons with obesity: results of the national ACTION study. Issue 5 (4th July 2019) - Look, Michelle; Kolotkin, Ronette L.; Dhurandhar, Nikhil V; Nadglowski, Joseph; Stevenin, Boris; Golden, Angela
ABSTRACT: Objective : Our aim was to explore how differing attitudes, expectations, and experiences among people with obesity (PwO) and healthcare providers (HCPs) might have an impact on effectively implementing current obesity treatment guidelines. Methods : Online surveys were conducted among 3, 008 adult PwO (BMI≥30 by self-reported height and weight) and 606 HCPs. Results : PwO with weight loss ≥ 10% during the previous three years were more likely to have been diagnosed with obesity and to have discussed a weight loss plan with an HCP. However, only 21% believe HCPs have a responsibility to actively contribute to their obesity treatment. Further, HCPs tend not to effectively communicate the diagnosis of obesity, its nature as a serious and chronic disease, the full range of treatment options, and obesity's implications for health and quality of life. Regarding treatment goals, HCPs more often focus on BMI reduction, while PwO's goals focus on improved functioning, energy, and appearance. HCPs also tend to underestimate their patients' motivation to address their obesity. Twenty-eight percent of HCPs 'completely agreed' that losing weight was a high priority for PwO, whereas more than half of PwO 'completely agreed' that losing weight was a high priority for them. When asked how their HCP could better support them, PwO most often expressed a desire for helpful resources, as well as assistance with specific and realistic goal-setting to improve health. Conclusions : HCPs can more effectively implement obesity treatment guidelines by more clearly and proactively communicating with PwO about their diagnosis, health implications of obesity, desired treatment goals, and the full range of treatment options. HCPs should understand that most PwO believe that managing their disease is solely their own responsibility. HCPs can also encourage more effective conversations by better appreciating their patients' motivation and treatment goals. Trial registration: ClinicalTrials.gov identifier: NCT03223493.